Effects of Extreme Salinity Stress on a Temperate Mangrove Ecosystem - Dittmann, Sabine; Mosley, Luke; Stangoulis, James; Nguyen, Van Lam; Beaumont, Kieren; Dang, Tan; Guan, Huade; Gutierrez-Jurado, Karina; Lam-Gordillo, Orlando; McGrath, Andrew (Frontiers in Forests and Global Change, 2022)
Mangrove forests provide essential ecosystem services, but are threatened by urban and industrial developments, effects of climatic change and chemical pollutants. When subject to cumulative pressures, an extreme event can trigger mangrove dieback. Although mangroves are adapted to saline habitats, hypersaline events can lead to mortality. A recent dieback event of >9 ha of temperate mangrove (Avicennia marina) in South Australia after hypersaline brine seepage allowed to evaluate the generality of anthropogenic impacts on mangrove ecosystems. Using a multidisciplinary approach, we compared characteristics of trees and soils in intact and degraded mangrove to detect the extent of the impact. The health of the mangrove forest was differentiated into ‘healthy’, ‘stressed’ and ‘dead’ zones using airborne LiDAR, RGB and hyperspectral imagery. Hyperspectral classification also detected background stress. Porewater salinities of >100 were measured in areas where mangrove dieback occurred, and hypersalinity persisted in soils a year after the event. Sulfate and chloride concentrations were also higher in deeper sediment of the ‘dead’ zone compared to other parts of the mangrove forest. The redox potential showed anaerobic conditions in all sediment depths of the ‘dead’ zone. There was high variability in CO2 efflux from sediment between the zones and survey months. The mangrove forest structure varied naturally from the seaward to the landward edge where the dieback occurred, but biomass and soil carbon stocks were not significantly different across the zones. NDVI, photosynthetic rate, stomatal conductance and transpiration rate as well as chlorophyll fluorescence were lower in the ‘stressed’ than ‘healthy’ mangrove zone. Leaves from mangrove in the ‘stressed’ zone had higher carbon but lower nitrogen content. Leaf nutrients were mostly higher in leaves from the ‘healthy’ zone, while leaves from the ‘stressed’ zone contained higher arsenic, sulfur and zinc concentrations. Our findings indicate an impact on mangrove health beyond the immediate dieback zone. The effects of an extreme hypersaline event recorded in our temperate semi-arid setting were similar to those recorded from the tropics and subtropics, indicating that the climatic region could be more important than latitude to place mangroves at risk from extreme hypersalinity.